Trends in the Utilization of Penile Prostheses in the Treatment of Erectile Dysfunction in the United States. (1st July 2015) - Lee, Daniel J.; Najari, Bobby B.; Davison, Wesley L.; Al Awamlh, Bashir Al Hussein; Zhao, Fujun; Paduch, Darius A.; Mulhall, John P.; Chughtai, Bilal; Lee, Richard K.
ABSTRACT: Background: The utilization of penile prosthesis (PP) insertion in the general population for medically refractory erectile dysfunction (ED) has not been well‐characterized. This study assessed the national temporal trends in the surgical management of ED utilizing PP. Materials and Methods: An analysis of the 5% Medicare Public Use Files from 2001 to 2010 was performed to assess the use of PP. Regression analysis was performed to identify factors associated with PP placement, type of PP utilized, and factors associated with revisions. Results: A total of 1, 763, 260 men were diagnosed with ED, 3% (53, 180) of whom underwent PP insertion. The utilization of PP for ED decreased from 4.6% in 2002 to 2.3% in 2010 ( P  < 0.01). This temporal decline in utilization was significant across all demographic factors including age, ethnicity, and geographic location. Men aged 65–74, from the U.S. South and West, and those with Charlson comorbidity scores >1 were more likely to have a PP inserted for ED ( P  < 0.01). African American men were more likely to have a semirigid PP placed compared with a multicomponent inflatable PP, and were more likely to undergo a revision or removal of the PP compared with Caucasian men ( P  < 0.01). Conclusions: The surgical management of ED with PP changed significantly between 2001 and 2010. The overall utilization of PP decreased, but its use in patients with significant medical comorbidities increased. Age >65, ethnicity, and geography influenced the likelihood of PP placement, prosthesis type, as well as the likelihood of prosthesis removal or revision.